Protective role of phyllanthus niruri extract against thioacetamide-induced liver cirrhosis in rat model - Amin, Zahra A.; Bilgen, Mehmet; Alshawsh, Mohammed A.; Ali, Hapipah Mohd; A. Hadi, A. Hamid; Abdulla, Mahmood Ameen (Hindawi, 2012)
A preclinical study was performed to determine if the extract from Phyllanthus niruri (PN) plays a protective role against liver cirrhosis induced by thioacetamide (TAA) in rats. Initially, acute toxicity was tested and the results showed that the extract was benign when applied to healthy rats. Next, the therapeutic effect of the extract was investigated using five groups of rats: control, TAA, silymarin, and PN high dose and low dose groups. Significant differences were observed between the TAA group and the other groups regarding body and liver weights, liver biochemical parameters, total antioxidant capacity, lipid peroxidation, and oxidative stress enzyme levels. Gross visualization indicated coarse granules on the surface of the hepatotoxic rats' livers, in contrast to the smoother surface in the livers of the silymarin and PN-treated rats. Histopathological analysis revealed necrosis, lymphocytes infiltration in the centrilobular region, and fibrous connective tissue proliferation in the livers of the hepatotoxic rats. But, the livers of the treated rats had comparatively minimal inflammation and normal lobular architecture. Silymarin and PN treatments effectively restored these measurements closer to their normal levels. Progression of liver cirrhosis induced by TAA in rats can be intervened using the PN extract and these effects are comparable to those of silymarin.